Further characterization of adult sheep ovarian stem cells and their involvement in neo-oogenesis and follicle assembly - Hiren Patel; Deepa Bhartiya; Seema Parte (BMC, 2018)
Abstract Background Stem cells in the ovary comprise of two distinct populations including very small embryonic-like stem cells (VSELs) and slightly bigger progenitors termed ovarian stem cells (OSCs). They are lodged in ovary surface epithelium (OSE) and are expected to undergo neo-oogenesis and primordial follicle (PF) assembly in adult ovaries. The ovarian stem cells express follicle stimulating hormone (FSH) receptors and are directly activated by FSH resulting in formation of germ cell nests (GCN) in vitro. Present study was undertaken to further characterize adult sheep OSCs and to understand their role during neo-oogenesis and PF assembly. Methods Stem cells were collected by gently scraping the OSE cells and were characterized by H&E staining, immuno-localization, immuno-phenotyping and RT-PCR studies. Expression of FSH receptors and markers specific for stem cells (OCT-4, SSEA-4) and proliferation (PCNA) were studied on stem/progenitor cells in OSE culture and on adult sheep ovarian cortical tissue sections. Effect of FSH on stem cells was also studied in vitro. Asymmetric cell division (ACD) was monitored by studying expression of OCT-4 and NUMB. Results Additional evidence was generated on the presence of two populations of stem cells in the OSE including VSELs and OSCs. FSHR expression was observed on both VSELs and OSCs by immuno-localization and immuno-phenotyping studies. FSH treatment in vitro stimulated VSELs that underwent ACD to self-renew and give rise to OSCs which divided rapidly by symmetric cell divisions (SCD) and clonal expansion with incomplete cytokinesis to form GCN. ACD was further confirmed by differential expression of OCT-4 in VSELs and NUMB in the OSCs. Immuno-histochemical expression of OCT-4, PCNA and FSHR was noted on stem cells located in the OSE in sheep ovarian sections. GCN and cohort of PF were observed in the ovarian cortex and provided evidence in support of neo-oogenesis from the stem cells. Conclusion Results of present study provide further evidence in support of two stem cells populations in adult sheep ovary. Both VSELs, OSCs and GCN express FSH receptors and FSH possibly regulates their function to undergo neo-oogenesis and primordial follicle assembly.